Cheyne-Stokes Breathing as a Predictive Indicator of Heart Failure in Patients With Obstructive Sleep Apnea; A Retrospective Case Control Study Using Continuous Positive Airway Pressure Remote Monitoring Data - Saito, Kimimasa; Takamatsu, Yoko (Frontiers in Cardiovascular Medicine, 2022)
Objective: We conducted a retrospective case control study to examine whether remote monitoring of Cheyne-Stokes breathing (CSB) was useful for predicting the onset of heart failure (HF) in patients with obstructive sleep apnea (OSA) on continuous positive airway pressure (CPAP). Methods: Among patients with OSA treated at our hospital, 33 patients with HF that occurred between July 2014 and May 2021 (11 patients with acute HF [AHF]; 22 patients with chronic HF [CHF] exacerbation) were included in the HF group. Of the 618 stable patients, 149 patients with a 30-day average CSB rate (CSB%) ≧1% were included in the non-HF control group. The chronologic change of CSB% were compared among the AHF, CHF and Control groups. Furthermore, of the 149 patients in the non-HF control group, 44 patients were matched for CSB%, body mass index, and sex in a ratio of 1:2 to 22 patients with CHF. The average cycle length (CL) of CSB was compared among three groups: CHF in stable period (CHF-stable group), CHF in exacerbation period (CHF-exacerbation group), and control group. In addition, according to the status of HF, receiver operating characteristic (ROC) curves were generated to determine the optimal cut-off points for variation of CSB% and CL. Results: Chronological change in CSB% among the three groups was significantly different. Standard deviation of CSB% (SD CSB%) before onset HF was significantly higher in both the AHF and CHF groups than in the control group. The CL of CSB was significantly longer in the CHF group than in the control group and was longer during the exacerbation period than during the stable period. The optimal cut-off value of CL that could differentiate patients with and without the onset of HF was 68.9 seconds. Conclusion: The HF group demonstrated greater CSB variations and longer CL than the non-HF control group. Furthermore, the CL was longer during the exacerbation period of HF even in the same patient. These results suggest that remote monitoring of CPAP device data for CSB variations and CL might allow early prediction of the onset and exacerbation of HF.